Predicting the Intention to Pursue Certified Professional Accountancy Qualification Among the Accounting Students - Chi, Tiw Kai; Sin Yi, Thai; Al Mamun, Abdullah; Hayat, Naeem; Salamah, Anas A.; Yang, Qing (Frontiers in Psychology, 2022)
The current study aimed to explore the formation of the intention to pursue certified professional accountancy qualification (CPAQ) with respect to the extended theory of planned behaviour (TPB). This study adopted a cross-sectional design and collected quantitative data from a total of 339 accounting students from Malaysia using an online survey. The finding of this study revealed that capabilities, career opportunities, job security, and stability appeared to influence the students' intention to pursue CPAQ. Meanwhile, attitude towards CPAQ, subjective norm, and perceived behavioural control had affected the students' decision to pursue CPAQ, which is in line with the TPB. This study concentrated on the importance of these factors in dictating the students’ intention and decision to pursue CPAQ. The study offered vital implications for accounting educators and educational institutions, where subject teachers or academic counsellors are assisted in their effort of helping the students to make a career choice of pursuing CPAQ. The Malaysian government should encourage and support accounting students financially for pursuing CPAQ through the provision of job security and enhancing subjective norm that may enable these students to complete the required professional qualifications. The limitations of study and future research opportunities are documented at the end of this paper.